2022
DOI: 10.1093/infdis/jiac160
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Matrix Metalloproteinase 8 Associates With Sputum Culture Positivity in Pulmonary Tuberculosis

Abstract: Current methods for tuberculosis (TB) treatment monitoring are suboptimal. We evaluated plasma matrix metalloproteinase (MMP) and procollagen III N-terminal propeptide concentrations before and during TB treatment as biomarkers. Plasma MMP-1, -8 and -10 significantly decreased during treatment. Plasma MMP-8 was increased in sputum Mycobacterium tuberculosis culture positive relative to culture negative participants, prior to (median 4993 pg/ml, IQR 2542-9188 vs 698 pg/ml, IQR 218-4060, p = 0.004) and after 6 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
2
4
0
1
Order By: Relevance
“…Elevated plasma MMP-8, together with MMP-3, -7, -10 and PIIINP associated with Mtb -BSI and mortality at 12 weeks, suggesting that MMP upregulation and matrix turnover are features of TB disease severity. This is in keeping with our recently reported finding that elevated plasma MMP-8 concentrations at the end of TB treatment are associated with persistent Mtb culture positivity (7). In the clustering analysis, MMP-8 was most closely associated with procalcitonin (an acute phase reactant) and the matrix degradation product, PIIINP (released during Type III collagen turnover), suggesting that MMP-8 activity, collagen turnover and acute inflammation are closely related processes in HIV-TB (5, 8).…”
Section: Discussionsupporting
confidence: 93%
“…Elevated plasma MMP-8, together with MMP-3, -7, -10 and PIIINP associated with Mtb -BSI and mortality at 12 weeks, suggesting that MMP upregulation and matrix turnover are features of TB disease severity. This is in keeping with our recently reported finding that elevated plasma MMP-8 concentrations at the end of TB treatment are associated with persistent Mtb culture positivity (7). In the clustering analysis, MMP-8 was most closely associated with procalcitonin (an acute phase reactant) and the matrix degradation product, PIIINP (released during Type III collagen turnover), suggesting that MMP-8 activity, collagen turnover and acute inflammation are closely related processes in HIV-TB (5, 8).…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that changes in the levels of these inflammatory mediators are linked with the early bactericidal effect during the first two months of intensive TB treatment. Similar results were observed in previous studies [ 18 , 19 , 23 , 29 , 31 , 32 ]. Neutrophil levels in blood correlated negatively with MMP-2 at baseline and month 6, and they also declined during TB treatment, with the opposite effect observed for MMP-2 levels.…”
Section: Discussionsupporting
confidence: 92%
“…Muefong and Sutherland (2020) described that levels of pro-inflammatory neutrophil-derived mediators in blood, such as MMP-1, -2, -3, -8 and -9, are linked to lung damage at baseline and lung recovery [ 18 , 22 ]. Consistent with these results, another study also showed that levels of certain neutrophil mediators decreased upon TB treatment initiation in a cohort of TB patients living with HIV; hence, such MMPs can be potential biomarkers for monitoring TB treatment regardless of HIV coinfection [ 23 ].…”
Section: Introductionmentioning
confidence: 58%
“…In this study, the prevalence of malnutrition in patients with bacterial positivity was significantly higher than bacteria negative, and bacterial positivity was a risk factor for malnutrition. Walker et al ( 78 ) observed that patients with bacterial positivity had significantly higher levels of inflammatory factors, such as matrix metalloproteinase 1 and matrix metalloproteinase 8, than negative patients, and the stronger the inflammatory response, the more active the catabolism, the greater the energy expenditure, and the greater the risk for malnutrition. Moreover, malnutrition can also lead to delayed sputum conversion ( 16 ).…”
Section: Discussionmentioning
confidence: 99%